Сучасні класифікації хронічних мієлопроліферативних захворювань: стандарти та тенденції вдосконалення - Лисенко, Д.А. (Iнститут експериментальної патології, онкології і радіобіології ім. Р. Є. Кавецького, 2008)
In work modern signs on classification of chronic myeloproliferative diseases are presented. The role oncogene in pathogenesis myeloproliferative diseases, their basic influence on development of pathology is covered. New approaches in classification chronic myeloproliferative diseases are described.